Multisocieties position paper: Microbiological surveillance on flexible endoscopes. Issue 9 (September 2021) - Casini, Beatrice; Pan, Angelo; Guarini, Alessandra; Rivara, Cinzia; Zullo, Angelo; Monica, Fabio; Cimbro, Monica; Casarano, Salvatore; Inglese, Agostino; Vaghi, Adriano; Schiffino, Luigi; Capezzuto, Erminio; et al.
Abstract: Transmission with endoscopes, particularly duodenoscope, of potential lethal infections prompted different scientific societies to deliver recommendations aimed reducing this risk. Some International societies extended recommendations on microbial surveillance to all the endoscopes and devices used in the reprocessing procedure. Considering the relevance of the topic, 8 Italian scientific societies of physicians, nurses and technical operators prepared a concerted document taking into account Institutional advisories and facilities in Italy. The rules for a correct microbial surveillance on endoscopes were detailed in term of what, how and when to perform the procedure, also suggesting behaviors in case of contamination.